ENHANCING BREAST SELF-EXAMINATION KNOWLEDGE AMONG ADOLESCENT GIRLS: A QUASI-EXPERIMENTAL STUDY OF AUDIOVISUAL AND LEAFLET-BASED EDUCATION IN JOMBANG, EAST JAVA, INDONESIA - Putra, Kusuma Wijaya Ridi; Sholikhah, Dwi Uswatun; Kurniawan, Vendi Eko (Indonesian Journal of Community Health Nursing, 2026)
Introduction: Breast cancer is the leading cause of cancer-related death among women, with cases increasingly found in younger populations. Early detection through breast self-examination (BSE) is an effective preventive measure, yet knowledge among Indonesian adolescents remains limited. This study aimed to examine the effectiveness of audiovisual and leaflet-based education in improving knowledge of BSE among adolescent girls.   Method: A quasi-experimental two-group pretest–posttest design was conducted among seventh- and eighth-grade female students at SMP Negeri 1 Peterongan, Jombang, Indonesia. From a population of 264 students, the sample size was determined using the Krejcie and Morgan formula, yielding 157 participants. To balance the groups, 160 students (80 per group) were recruited. Proportional random sampling was applied. Knowledge levels were measured using a validated questionnaire. Data were analyzed using the Wilcoxon signed rank test and One-Way ANOVA.   Result: Before intervention, most students in the audiovisual group demonstrated poor knowledge (52.5%), while most in the leaflet group had moderate knowledge (50%). After intervention, knowledge levels significantly improved in both groups (p < 0.001). In the audiovisual group, 90% achieved good knowledge, whereas in the leaflet group, 60% maintained moderate knowledge. One-Way ANOVA confirmed a significant difference between groups (p < 0.001), with audiovisual media showing greater effectiveness.   Conclusion: Audiovisual education proved more effective than leaflet-based education in enhancing adolescent girls’ knowledge of BSE. Integrating audiovisual methods into school health programs may strengthen early breast cancer awareness and prevention efforts among young populations.   Keywords: Breast self-examination, adolescent girls, audiovisual media, leaflet, health education.